Factors Affecting Platelet Yield in a Single Donor Plateletpheresis - Tooba Fateen, Saima Farhan, Faiza Shafqat, Nazish Saqlain, Seema Butt, Faryal Abid, Muhammad Ahsan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: This procedure, known as plateletpheresis, involves the removal of platelets from a donor's blood. This method produces eight times as many platelets as would be obtained by using whole blood. Aim: To evaluate the effect of different donor related factors on platelet yield. Method: This research was carried out at the Children's Hospital & Institute of Child Health Science in Lahore, Pakistan, specifically in the Immunohematology & Blood Transfusion Unit. Forty plateletpheresis donors meeting the criteria were enlisted for the study. The COM.TEC cell separator apparatus and the TRIMA automated blood collection system were used to perform the plateletpheresis. Before and after a plateletpheresis, the patient's hematocrit, haemoglobin, platelet count, white blood cell count, processed volume, and processing time were recorded. Results: Platelet yield demonstrated a substantial positive link with the pre-platelet count of the donors, as well as their age, weight, and the volume processed. Platelet production was not correlated in any way with blood group, total leukocyte count, high-content testing, or processing time. Conclusion: A patient's pre-platelet count, age, weight, and processed volume were positively correlated with their platelet production. Keywords: Plateletpheresis, Hemoglobin, Total leukocyte count, Platelet count, Platelet yield